Profitability of Investment Strategies Based on Stock Recomendations on the Polish Market - Zaremba, Adam; Konieczka, Przemysław (Studia Oeconomica Posnaniensia, 2015)
The profitability of analysts’ recommendations is documented in numerous studies from all over the world. However, the evidence from the Polish market is relatively modest. The primary aim of this study is to fill this gap. The paper contributes to the economic literature in three ways. First, it provides fresh out-of-sample evidence on returns patterns following analysts’ recommendations from Poland. Second, it examines the relationships between these patterns and the size of the analysed companies. Finally, it investigates whether it is possible to design profitable strategies based on the patterns discovered. We use monthly stock level data from Poland and the sample period is 2004-2013. In order to examine the profitability of analysts’ reports, we build long/short investment portfolios and test their performance against the CAPM, Fama-French three-factor, and Carhart four-factor models. The principal findings can be summarized as follows. First, we document that top-rated companies deliver better returns than bottom-rated companies. Second, we find that this profitability is particularly impressive among small-capitalisation companies. Third, the above-average rates of return can be partially explained by the influence of WML and HML factors. Finally, we provide evidence that strategies based on analysts’ recommendations deliver positive and statistically significant abnormal rates of return.